Psichodiagnostika v komandnych vidach sporta kak sredstvo operativnoj korrekcii trenirovocnogo processa - Tiunova, O. V.; Shirkovets, E. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The article presents the results of monitoring the psycho-physical condition of the Rugby team during the training camp, which includes a set of indicators prescribed by the industry regulations of psychological testing in the current survey of athletes. The analysis of the dynamics of the following indicators: health, activity, mood, level of situational anxiety and confidence, the degree of mental fatigue and overall performance, as well as the desire to train and compete. Recorded and the pulse of rest in the morning after waking up. Monitoring was carried out by athletes independently in strict accordance with the developed technology of self-observation and self-control. Statistical processing of the results confirmed the informativeness of the monitoring technique used, allowed to assess the features of adaptation to loads at a certain stage of preparation of athletes and to make the necessary adjustments to the plan of their further training.